Hopkins’ Counter Stress - Pizza, Joseph (Literature and theology, 2011)
The following article explores what I.A. Richards termed ‘the Belief problem’ in Gerard Manley Hopkins’ poetry and poetics. In particular, Hopkins’ descriptions of sprung rhythm are examined in the context of his response to John Henry Newman’s lecture ‘On Catholic Literature in the English Tongue’. Following from this discussion, the interrelation of religion and rhythm in Hopkins’ work is reconsidered, and the challenges it poses to critics confronted.